PANDANGAN AL-QUR'AN TENTANG ETOS KERJA - Sudin Yamani; Achmad Abubakar (Sekolah Tinggi Pariwisata Mataram, 2022)
Religion.Islam.is religion. which.has .doctrine .which is .general .and complete..Say. Ethics in language. is a word that comes from the Greek language, namely ethos which means belief in something, and in terms the word ethics or ethos means a view of life or a tool in the form of norms related to behavior that is sought to achieve something perfect. The nature of work for every Muslim is considered as an act of worship. As an expression of gratitude and a form of sacrifice for the Creator from his servant and is an expression of gratitude where every Muslim can know that the creation of the earth and everything in it is a test and trial for humans with noble character. Every work must be intended to Allah swt not only to fulfill economic needs. Therefore, the work carried out must be done in a way that is justified by religion so that Allah swt always opens the door of rijkio from all directions that were not previously expected.